2023
DOI: 10.1371/journal.pone.0287326
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for medical device-related pressure injury in ICU patients: A systematic review and meta-analysis

Ling Gou,
Zhiqin Zhang,
Yongde A.

Abstract: Background Medical device-related pressure injury (MDRPI) in intensive care unit (ICU) patients is a serious issue. We aimed to evaluate the risk factors for MDRPI associated with ICU patients through systematic review and meta-analysis, and provide insights into the clinical prevention of MDRPI. Methods We searched PubMed, Embase, Web of Science, China National Knowledge Infrastructure (CNKI), WanFang Database, and China BioMedical Literature Database (CBM) (from inception to January 2023) for studies that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“… 1 , 2 MDRPI accounts for 29.0% to 34.5% of hospital‐acquired pressure injuries. 3 , 4 Non‐invasive ventilation is the equipment of choice for the treatment of acute respiratory failure, which can efficiently enhance lung ventilation, alleviate respiratory muscle fatigue and rectify respiratory failure. 5 , 6 , 7 Multiple studies 8 , 9 , 10 have shown that patients using non‐invasive ventilation need to wear nasal masks or oronasal masks for a long time, which increases the risk of pressure damage in the region of facial bone prominence.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 MDRPI accounts for 29.0% to 34.5% of hospital‐acquired pressure injuries. 3 , 4 Non‐invasive ventilation is the equipment of choice for the treatment of acute respiratory failure, which can efficiently enhance lung ventilation, alleviate respiratory muscle fatigue and rectify respiratory failure. 5 , 6 , 7 Multiple studies 8 , 9 , 10 have shown that patients using non‐invasive ventilation need to wear nasal masks or oronasal masks for a long time, which increases the risk of pressure damage in the region of facial bone prominence.…”
Section: Introductionmentioning
confidence: 99%